The Relationship Between Leadership And Organizational Behavior (Case Study Of Ketapanrame Village Government) - Seftiasari, Gita; Trisnawati, Juliani Dyah (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2024)
Leadership and organizational behavior are two crucial elements in any organization, including in the context of village governance. Good leadership not only influences the direction and goals of the organization but also shapes the culture and dynamics within it. Understanding organizational behavior in Ketapanrame Village is essential to identify the patterns of interaction between individuals and groups, as well as how local culture affects the performance of village officials and the community. In this context, the relationship between leadership and organizational behavior is the main focus of this study. The research uses a qualitative approach with a case study method to explore the dynamics in more depth. Data were collected through in-depth interviews, direct observation, and analysis of relevant documents. The findings show that the relationship between leadership and organizational behavior in Ketapanrame Village has a direct impact on the effectiveness of village governance. Effective leadership can foster positive organizational behavior, where leaders create an environment that encourages collaboration, open communication, and innovation. Conversely, positive organizational behavior will support the achievement of the organization’s vision and mission, as well as improve overall performance, creating synergy between leaders, village officials, and the community